2004
DOI: 10.1021/ja040051m
|View full text |Cite
|
Sign up to set email alerts
|

Semiquinone Footprinting

Abstract: The first examples of anion radical cycloaddition induced by homogeneous electron transfer from chemical agents are described. Specifically, upon exposure to chrysene anion radical, bis(enone) substrates are found to engage in stereoselective intramolecular [2 + 2] cycloaddition. These studies, along with the corresponding electrochemically initiated reactions, provide insight into this fundamentally new pattern of reactivity and support the feasibility of expanding this novel reaction type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Peptides incorporating such motifs possess excellent DNA binding capability in the sub-micromolar concentration range. [11][12][13][14][15][16] Further attachment of one or more 4-amino-1-methylpyrrole-2-carboxylic acid resi-dues (Py) to XP(Hyp)RK peptides enhances their sequencespecificity toward sequences containing consecutive arrays of A or T nucleotides. 11,[14][15][16] Here we report that peptides HyM-10 and HQ-10 bind satisfactorily to DNA in a sequence-selective manner as assessed by DNase I footprinting.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides incorporating such motifs possess excellent DNA binding capability in the sub-micromolar concentration range. [11][12][13][14][15][16] Further attachment of one or more 4-amino-1-methylpyrrole-2-carboxylic acid resi-dues (Py) to XP(Hyp)RK peptides enhances their sequencespecificity toward sequences containing consecutive arrays of A or T nucleotides. 11,[14][15][16] Here we report that peptides HyM-10 and HQ-10 bind satisfactorily to DNA in a sequence-selective manner as assessed by DNase I footprinting.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Extensive studies have been carried out with small ligands that are capable of sequence-specific recognition of DNA including drugs, 1-3 antitumor antibiotics, [4][5][6][7] netropsin/distamycin and its analogues, [8][9][10][11][12][13] and synthetic peptides. [14][15][16][17] Previously we introduced a novel XPRK peptide motif as a basis for sequence-selective interaction studies. [14][15][16][17] The design of this motif stems from a naturally occurring SPXX motif 18,19 found in repeating sequences in histones, steroid hormone receptors, various segmentation gene products and some oncogene products.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Previously we introduced a novel XPRK peptide motif as a basis for sequence-selective interaction studies. [14][15][16][17] The design of this motif stems from a naturally occurring SPXX motif 18,19 found in repeating sequences in histones, steroid hormone receptors, various segmentation gene products and some oncogene products. It was suggested that the SPXX motif assumes a b-turn stabilized by two hydrogen bonds, and that the side chains of the two basic residues engage in salt bridges with the DNA phosphate groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation